Optimasi Alokasi Waktu Proses CPU Pada Linux dengan Algoritma Priority Scheduling: Mutasar - Mutasar (Jurnal Elektro dan Informatika, 2020)
Scheduling is related to the problem of deciding which processes will be carried out in a system. Processes that have not received the allocation from the CPU will queue in the ready queue. The scheduling algorithm is used to determine which processes are in the ready queue to be executed by the CPU.